Decompositions of Single-Valued Neutrosophic Continuity via Primalization (Contemporary Mathematics, 2025)
This paper introduces new single-valued neutrosophic closure operators based on single-valued neutrosophic primals, laying the foundation for single-valued neutrosophic primal topologies. This framework establishes a novel class of topological spaces, termed single-valued neutrosophic primal topological spaces. Within this context, classical topological concepts are redefined to align with the properties of single-valued neutrosophic primal set-topologies. The study explores the basic structure of these topologies, including the construction of bases, and examines relationships between various single-valued neutrosophic primal and single-valued neutrosophic topologies. A significant contribution of this work is the introduction of single-valued neutrosophic primal continuous functions, supported by counterexamples to illustrate their implications and nuances.
Keywords: Single-valued neutrosophic primal; single-valued neutrosophic (closure, interior, per-primal interior, α-primal interior, β-primal closure, β-primal interior) operators; single-valued neutrosophic primal α-continuity; single-valued neutrosophic primal continuity